2015
DOI: 10.1016/j.tetlet.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of furans and pyrroles via migratory and double migratory cycloisomerization reactions of homopropargylic aldehydes and imines

Abstract: A novel gold-catalyzed divergent sysnthesis of furans and pyrroles employing readily available homopropargylic aldehydes and imines have been developed. The regiochemical outcome of this reaction is dependent on the substituent on the terminal alkyne of substrate. Thus, substrates possessing alkyl and aryl substituent at the alkyne moiety produce 2,3,5-substituted furans and pyrroles via a migratory cycloisomerizaton reaction. Whereas, their silicon analogues are capable to undergo a double migratory process l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Further expansion of this concept to homopropargylic ketones or imines led to reactions involving double rearrangements. 54 When studying gold-catalyzed [(C 6 F 5 ) 3 PAuSbF 6 ] reactions with substrates of type 122 possessing a cyclic substituent at propargylic position, the formation of the fused ring 129 was observed (Scheme 18). 54 It was suggested that this reaction proceeds via an initial activation of the triple bond followed by cyclization to obtain Similarly, dihydrofurans 132 can be obtained by combining alkynylsilanes 130 and the corresponding aldehydes 131 (Scheme 19).…”
Section: Scheme 17 Synthesis Of Furans From Alkynylsilanesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further expansion of this concept to homopropargylic ketones or imines led to reactions involving double rearrangements. 54 When studying gold-catalyzed [(C 6 F 5 ) 3 PAuSbF 6 ] reactions with substrates of type 122 possessing a cyclic substituent at propargylic position, the formation of the fused ring 129 was observed (Scheme 18). 54 It was suggested that this reaction proceeds via an initial activation of the triple bond followed by cyclization to obtain Similarly, dihydrofurans 132 can be obtained by combining alkynylsilanes 130 and the corresponding aldehydes 131 (Scheme 19).…”
Section: Scheme 17 Synthesis Of Furans From Alkynylsilanesmentioning
confidence: 99%
“…54 When studying gold-catalyzed [(C 6 F 5 ) 3 PAuSbF 6 ] reactions with substrates of type 122 possessing a cyclic substituent at propargylic position, the formation of the fused ring 129 was observed (Scheme 18). 54 It was suggested that this reaction proceeds via an initial activation of the triple bond followed by cyclization to obtain Similarly, dihydrofurans 132 can be obtained by combining alkynylsilanes 130 and the corresponding aldehydes 131 (Scheme 19). 55 The reaction tolerates a variety of Ar 1 substituents, phenyl and heterocyclic motifs with both electron-withdrawing and -donating effects, affording the desired product in good to excellent yields.…”
Section: Scheme 17 Synthesis Of Furans From Alkynylsilanesmentioning
confidence: 99%
“…It was demonstrated that functional groups such as methoxy, fluoro, nitro and nitrile could be well-tolerated under these reaction conditions, affording the C2-unsubstituted 3-silylfurans 2F-Si′ as sole regioisomer in good yields. It is supposed that the migration might proceed through a β-silyl palatium carbene intermediate, wherein the 1,2-Si migration is kinetically favored over the 1,2-H [50][51][52][53] (See Supplementary Material for the proposed reaction mechanism). To synthesize 2-silyl-bifurans, a stepwise strategy was adopted with TBS-protected enynals as starting material.…”
Section: Scope Of the Investigationmentioning
confidence: 99%
“…Recently, Gevorgyan and co‐workers described a synthetic route toward furans and pyrroles via migratory cycloisomerization sequences (Scheme ) . To this end, homopropargylic aldehydes and imines ( 39 ) were converted in the presence of gold(I)‐catalysts, and the corresponding heterocycles 40 and 41 were isolated.…”
Section: 2‐alkyl Migrationmentioning
confidence: 99%
“…[38] Recently, Gevorgyan and co-workers described a synthetic route toward furans and pyrroles via migratory cycloisomerization sequences (Scheme 17). [39] To this end, homopropargylic aldehydes and imines (39) were converted in the 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 presence of gold(I)-catalysts, and the corresponding heterocycles 40 and 41 were isolated.…”
Section: 2-alkyl Migrationmentioning
confidence: 99%